English Development-Based Instructional Materials 2013 Integrating Curriculum Values in the Junior National Character - Zuhriyah, S.S., M.Pd, Aminatuz (Program Studi Ilmu Komunikasi, 2015)
This research is the development of research designed using a 4-D models of development the which consists of four stages items, namely; the definition phase, design phase, development phase, and dissemination phase.The subjects were teachers and students in lower secondary levelEast Java, namely SMP Bhinneka Tunggal Ika Purwosari.The Data were collected through observation, questionnaires, and tests. Based on the results of field testing, teaching materials produced have met the criteria of practicality and effectiveness.